(ANT)agonistics: Pluralistic politicization of, and by, accounting and its technologies. (September 2016) - Vinnari, Eija; Dillard, Jesse
Abstract: Agonistics has been put forth as a theoretical/conceptual basis for developing more democratic forms of accounting, such as dialogic accounting. However, an area of agonistics based dialogic accounting that requires further theorization is "the moment of decision"—how the democratic discussion and debate can maintain its pluralistic ethos while being focused in such a way as to ultimately lead to choosing and implementing an action. In developing a richer theorization of agonistic dialogic accounting, we engage actor–network theory, particularly the due process envisioned in Bruno Latour's Politics of Nature (2004a). In doing so, we contribute to the critical accounting literature focusing on agonistic dialogic accounting by introducing Latour's bicameral parliament and by refining Brown's dialogic accounting principles. As a secondary contribution, our (ANT)agonistic framework responds to the calls for more democratic forms of governance in the context of accounting. We illustrate our theoretical framework with an example regarding the development of integrated reporting.